Dual Chemical Modification of a Polytheonamide Mimic: Rational Design and Synthesis of Ion‐Channel‐Forming 48‐mer Peptides with Potent Cytotoxicity. Issue 10 (2nd February 2016) - Hayata, Atsushi; Itoh, Hiroaki; Matsutaka, Shoko; Inoue, Masayuki
Abstract: Polytheonamide B (1 ) is a natural peptide that displays potent cytotoxicity against P388 mouse leukemia cells (IC50 =0.098 nm ). Linear 48‐mer1 is known to form monovalent cation channels on binding to lipid bilayers. We previously developed a fully synthetic route to1, and then achieved the design and synthesis of a structurally simplified analogue of1, namely, dansylated polytheonamide mimic2 . Although the synthetically more accessible2 was found to emulate the channel function of1, its cytotoxicity was decreased 120‐fold. Herein, the chemical preparation and biological evaluation of seven analogues3 –9 of2 are reported. Compounds3 –9 were modified at their N terminus and/or the side chain of residue 44 of2 to alter their physicochemical properties. The total synthesis of3 –9 was accomplished in a unified fashion by a combination of solid‐phase and solution‐phase chemistry. Systematic evaluation of the hydrophobicities, single‐channel currents, ion‐exchange activities, and cytotoxicities of3 –9 revealed that their hydrophobicities are correlated with the total magnitude of ion exchange and determine their cytotoxic potency. Consequently, the most hydrophobic analogue9 exhibited the lowest IC50 value, which is comparable to that of1 . Therefore, these results clarified that the bioactivity of the polytheonamide‐based peptides can be rationally controlled by changing their hydrophobicity at the N and C termini of the 48‐amino‐acid sequence. Abstract : Simpler but potent : Total synthesis and multiple functional analyses of seven new structurally simplified analogues of polytheonamide B, an ion‐channel‐forming 48‐mer peptide, are reported. Structure–activity studies clarified that the bioactivity of the analogues can be rationally controlled by changing their hydrophobicity at residues 1 and 44 (see figure). The most hydrophobic analogue exhibited the highest cytotoxicity, which is almost as potent as that of polytheonamide B.